FAKTOR-FAKTOR PEMENGARUH AUDIT REPORT LAG (Studi Empiris pada Perusahaan-Perusahan di Bursa Efek Indonesia) - Hariani, Diana; Darsono, Darsono (Diponegoro Journal of Accounting, 2014)
This study aims to find empirical evidence and analyze the factors that affect the audit report lag , this study is the replication of the research that has been done by Modugu ( 2012) in Nigeria, to conduct research on the differences in location, objects, samples, and additional variables independent life of the listing, because there are differences in the age variable listing the results of previous studies, in addition to supporting the influence of agency theory, which states that the cepet in the publication of the financial statements will menghilangan error information asymmetry. This is due to the condition that the company is a long listing on the Indonesia Stock Exchange is a company that has a lot of concern to stakeholders so as to encourage the importance of information management and want faster audited financial statements to be published.The population in this study are all companies listed on the Stock Exchange, the overall sample of 299 companies in 2011 and 318 samples in 2012 company, is a model of analysis used multiple regression analysis models. This study divides into six hypotheses, which analyzes the effect of firm size, capital structure, profitability, the complexity of the company's operations, the age listing on audit report lag, and analyze different types of industries on audit report lag.This study shows that company size, profitability and complexity of the company's operations significantly affect the audit report lag. Agency theory can be integrated as a research model. The findings of this study recommends increased insight and knowledge of the dominant factors that cause the audit report lag, and also can be considered for investment.